Submerged antiquities on Paros and Naxos (Cyclades, Greece). New evidence for the mean sea level during the Late Bronze age and the Roman period. - Evelpidou, N.; Tziligkaki, E.; Karkani, A. (SLALOM International Conference, 2012)
A common feature of the coastal excavations in both Paros and Naxos is that of submerged antiquities and collapsed hilltops into the sea. Beach rocks along the modern coastlines bear witness to the extent and depth of ancient shores. The submerged antiquities of Paros include cemeteries of various time periods, harbor installations and certain rock-cut features whose function is not yet interpreted with certainty. The archaeologists who excavated Grotta and Aplomata on Naxos spoke of two seismic events; one at an early phase of the LH IIIA2 and another one at LH IIIC period. Indisputable evidence for those earthquakes offer two submerged tidal notches found at a depth of –3 m and –2.5 m respectively. The tsunami that covered the northern part of the Hellenistic Agora in the 2nd c. AD is additionally confirmed by a submerged tidal notch at a depth of –1.70 m and dated shells of Cerastoderma. The article proposes an entirely new perspective on the sea-level changes in Cyclades, which is strictly based on archaeological stratification and sea-level indicators.